2004
DOI: 10.1021/jo049158i
|View full text |Cite
|
Sign up to set email alerts
|

A Fine-Tuned Molybdenum Hexacarbonyl/Phenol Initiator for Alkyne Metathesis

Abstract: A new, highly potent activator for molybdenum hexacarbonyl and 2-fluorophenol is described. An "instant"catalyst formed in situ from molybdenum hexacarbonyl and 2-fluorophenol shows high activity for cross- and ring-closing alkyne metathesis reaction. The use of 2-fluorophenol can be combined with other activation methods to allow alkyne metathesis at relatively low temperature (80 degrees C).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 30 publications
1
33
0
Order By: Relevance
“…Such a catalyst system was initially discovered by Mortreux, [7,52] and later improved and widely used by Bunz, [4,53,54] Mori, [55] Fürstner [3] and more recently Grela. [56,57] This "instant" method is attractive because all the ingredients are inexpensive, commercially available and stable "off the shelf" reagents can be used directly without the rigorous purifications and an inert atmosphere. [58] However, this catalytic system shows poor compatibility with some heteroatom functional groups, such as esters, aldehydes, pyridines etc.…”
Section: 126mentioning
confidence: 99%
See 1 more Smart Citation
“…Such a catalyst system was initially discovered by Mortreux, [7,52] and later improved and widely used by Bunz, [4,53,54] Mori, [55] Fürstner [3] and more recently Grela. [56,57] This "instant" method is attractive because all the ingredients are inexpensive, commercially available and stable "off the shelf" reagents can be used directly without the rigorous purifications and an inert atmosphere. [58] However, this catalytic system shows poor compatibility with some heteroatom functional groups, such as esters, aldehydes, pyridines etc.…”
Section: 126mentioning
confidence: 99%
“…More recently, Grela and co-workers surveyed a variety of phenols as catalyst additives and identified 2-fluorophenol and 2-fluoro-5-methylphenol as optimal. [57] Despite considerable optimization on this catalyst system, its relatively harsh operative conditions as well as the low activity towards highly functionalized substrates present limitations in its wide application in organic synthesis and polymer chemistry. Moreover, the exact nature of the catalytically active species is still not clear.…”
Section: 126mentioning
confidence: 99%
“…more acidic halogeno-substituted phenols are much better than phenol, as found earlier on Mo(CO) 6 /ArOH-based catalysts [17,18], although no direct relationship between the activity and the pKa value of the co-catalysts could be found. This is similar to what was observed in several cases where a systematic study of the reactivity of in situ generated catalysts was conducted.…”
Section: Effect Of Different Co-catalysts On the Reaction Ratementioning
confidence: 52%
“…Phenol itself and chlorophenol, as well as silanols and fluoro alcohols were rapidly recognized as suitable to activate the reaction, and revealed that such hydroxylcontaining compounds were essential for the reaction to proceed [17]. Following this paper, several reports aimed at the search for the best co-catalyst to be used for these in situ systems have appeared in the literature, for classical metathesis reactions conducted on disubstituted alkynes [18], and also for comparisons between the MoO 2 (acac) 2 /AlEt 3 /ArOH and the Mo(CO) 6 /phenol catalytic systems applied to polymerization reaction of aromatic diynes [19]. In this paper were also reported data where different fluoro-substituted phenols were used, confirming that the use of different co-catalysts results in different reaction rates.…”
Section: Effect Of Different Co-catalysts On the Reaction Ratementioning
confidence: 99%
See 1 more Smart Citation